American Spirits : The Famous Fox Sisters and the Mysterious Fad that Haunted a Nation - Rosenstock, Barb (New York : Calkins Creek, an imprint of Astra Books for Young Readers, 2025)
"Rap. Rap. Rap. The eerie sound was first heard in March of 1848 at the home of the Fox family in Hydesville, New York. The familys two daughters, Kate and Maggie, soon discovered that they could communicate with the spirit that was making these uncanny noises. This strange incident, and the ones that followed, generated a media frenzy beyond anything the Fox sisters could have imagined"--
Keywords: Fox, Margaret, -- 1833-1893 -- Juvenile literature; Jencken, Catherine Fox, -- 1836-1892 -- Juvenile literature; Underhill, A. Leah; 1814-1890 -- Juvenile literature; Fox, Margaret, -- 1833-1893.; Jencken, Catherine Fox, -- 1836-1892.; Underhill, A. Leah; 1814-1890.; Spiritualism -- New York (State); Juvenile literature; United States; Juvenile literature; Parapsychological and occult techniques